A study on partnering and strategic alliances in the shipping industry - Tan, Daniel Wei Song. (2012)
This report hopes to explore the importance of strategic alliances. It would be exploring from the angle of reasons why companies would like to enter alliances; discussing what factors are crucial for successful alliances and finally gives a forward view of considerations of entering alliances would be like in the future. This is part of three segment study which will emphasis on the following pointers: Legal implications and synergy (Reasons for alliances); Role of management decision makers and legally binding contract (success/failure in alliances); and the future drivers of partnering and alliances.